Origin and Operation of the Chinese Academy of Engineering: An Interaction between Expertise and Politics. Issue 1 (2nd January 2020) - Wang, Nan
ABSTRACT: The Chinese Academy of Engineering (CAE) is one of the most important engineering institutions for Chinese engineers. The formal establishment of CAE, from its original conception in 1978 to its final birth in 1994, took almost 20 years. At present it has been in existence for two decades. Both the former decades-long emergence and the latter decades-long operation of CAE can be interpreted in terms of an interaction between expertise and politics. To understand the CAE's origins and operation, this paper will first examine how 'engineering' and 'engineer' have slightly different meanings in the historical and cultural context of China than in the West. Then it will focus on the decades-long creation of the CAE. In the 1970s, the proposal for a Chinese engineering academy was initiated by scientist and engineer members of the Chinese Academy of Science, as a result of both domestic and international influences. Through the 1980s and 90s, a few politicians jointly with those scientists and engineers made a crucial contribution to the founding of the CAE. Finally, the article offers an account of CAE's structure and operation during the first twenty years of its existence.